Identification Safety Critical Elements and Establish Performance Standards to Control Major Accident Hazard at The Geothermal Power Plant PT. XYZ - Febriardy, Febriardy; Fatriansyah, Jaka Fajar; Endang, Endang; Bagaskoro, Farhan Iqbal; Kurniawan, Ari (UI Scholars Hub, 2025)
Geothermal Power Plant (GPP) use steam from geothermal reservoirs to produce electricity. Power Plants are one of the most dangerous work environments. The dangers that exist in the power generation process can be in the form of Major Accident Hazard (MAH) and have a large impact which can cause Major Accidents. Major Accident prevention can be done by managing Safety Critical Elements (SCE) as a control measure in the form of procedures to prevent or mitigate the risks. Each SCE has a Performance Standard that includes targets and thresholds set to reduce risk to reach ALARP (As Low as Reasonably Practicable) that will be used as a reference in Inspection, Testing and Preventive Maintenance programs to prevent Major Accidents. This research was conducted to identify SCE and establish Performance Standard for GPP PT XYZ with a capacity of 1x55 MW. Based on the identification results, it is known that the total MAH at GPP PT XYZ is 112. Each MAH was analyzed using a bow-tie diagram to obtain a total of 532 SCE or 8.12% of the total 6,549 existing equipment.